Gribushin’s house: place, time and figures - Korchagin, P.A. (Perm Federal Research Centre Journal, 2024)
The Perm Federal Research Center of the Ural Branch of the Russian Academy of Science is located in the building that is a cultural heritage site called "the House of merchant Gribushin with a fence and gates", also known as "the House with Caryatids". The history of the house has been studied by many historians and literary scholars, as it exists in two qualities: physical and literary. The article explores the history of the building and the legends associated with it. Special attention is paid to the figures (caryatids) of the house, its owners and inhabitants. As a result of the study, it was possible to establish that the house originated much earlier than expected, no later than 1863, and the name of its first owner.